Employment and farmers' work in European ruminant livestock farms: A review. (February 2020) - Hostiou, N.; Vollet, D.; Benoit, M.; Delfosse, C.
Abstract: Agricultural employment, in sharp decline in Europe, is the subject of little recent scientific work, and few studies focus specifically on livestock farming. Labour and employment factors must be considered to respond appropriately to the livestock farming "crisis" in Europe and to assess the room to manoeuvre of public policies to adapt this sector to the diverse challenges facing it. We have conducted a review to assess the combined effects on ruminant livestock employment and famers' work at the European level. In the first section, employment in ruminant livestock farms is quantified and the main differences between livestock sectors and regions are identified. We have showed that in France, livestock activities mobilize 41% of the French agricultural workforce at the national level, but due to territorial diversity, there are significant variations across the country. In Europe, while all countries are affected by a reduction in the livestock workforce, employment trends also vary depending on the animal sector. In the second section, we analyse trends in farmers' work that could explain the evolution of agricultural employment in terms of slowing or accelerating the reduction in the livestock workforce. Our results highlighted supply-driven factors and demand-driven factors tend to increase the number of livestock workers. Some structural and institutional changes play a greater role as both an accelerator and moderator of the decline in livestock workers. The third section focuses on the effects of livestock employment on other industries. We show that the indirect and induced effects of livestock farming vary according to activity sector. Dairy farms have higher induced effects, especially at the national level. The development of processing activities can be limited locally by the low appeal of most of the jobs. In the conclusion, we highlight four major issues concerning employment and work in the livestock sector at the European level. Highlights: In Europe, mixed livestock and mixed crop-livestock farms have the largest employment decline. In Europe, the number of livestock farmers fell, except in Spain and the Netherlands. Supply-driven factors and demand-driven factors tend to increase the number of livestock workers. Some structural and institutional changes play a greater role for the decline in livestock workers. The indirect and induced effects of livestock farming vary according to activity sector : dairy farms have higher induced effects.